Dried blood spots: An evaluation of utility in the field - Xu Su; Bradley F. Carlson; Xiexiu Wang; Xiaoyan Li; Ying Zhang; JoLynn P. Montgomery; Yaxing Ding; Abram L. Wagner; Brenda Gillespie; Matthew L. Boulton (Elsevier, 2018)
Background: Use of dried blood spots (DBS) offers advantages over serum samples in studies conducted in resource-poor settings. The aim of this study was to compare the number of adequate spots collected across different demographic groups. Methods: Five DBS were collected from 3316 individuals aged 0-49 years in Tianjin, China for a measles antibody study; DBS were rated "adequate" or "inadequate." Linear regression, with the number of adequate DBS on a card as the outcome variable, was used to test for predictors of DBS adequacy. Results: There were 0 adequate DBS for 23% of participants and 5 adequate DBS for 24%. Mean number of adequate DBS was 1.68 in infants (<12 months), 2.57 (1-9 years), 3.49 (10-29 years), 3.08 (30-49 years). The number of adequate DBS increased over the study; the mean number of adequate DBS for the five years 2011-2015 were 1.21, 2.52, 3.40, 2.22, and 3.62, respectively. DBS quality was not related to measles IgG antibodies. Conclusions: DBS are an alternative for adults and children but pose challenges in infants, and improve with experience. In a resource-limited environment or in a scenario where more invasive techniques like venipuncture may be less accepted by the study population, DBS can be the preferred technique to efficiently obtain serum specimens for analyte testing. Keywords: Measles, China, Dried blood spots, Seroprevalence, Disease elimination